Peroxiredoxin 4 Interacts With Domeless and Participates in Antibacterial Immune Response Through the JAK/STAT Pathway - Ran, Xiao-qin; Gao, Lin; Yan, Meng; Kang, Cui-jie (Frontiers in Immunology, 2022)
The JAK/STAT pathway plays an important role in the development and immune responses of animals. In vertebrates, families of cytokines or growth factors act as activators of the JAK/STAT pathway; however, the activators for the JAK/STAT signaling pathway in arthropods are largely unknown. Herein, we report a new ligand, peroxiredoxin 4 (Prx4), for the Domeless in the JAK/STAT pathway of shrimp Marsupenaeus japonicus. Prx4 was induced to secret into the extracellular surroundings upon Vibrio challenge, which then facilitated the anti-Vibrio activity of shrimp by activating the phosphorylation and nuclear translocation of STAT and the expression of STAT-responsive antimicrobial peptides. Blocking the expression of Prx4 in vivo abrogated the activation of JAK/STAT pathway by Vibrio infection while injection of Prx4 protein activated the pathway. The interaction between Prx4 and Domeless was proved by immuno-precipitation and protein pull-down assays. Moreover, two cysteine residues in Prx4 that are critical for the interaction and Prx4’s anti-Vibrio role were identified, and the binding site in Domeless for Prx4 was proved to be the cytokine binding homology module (CBM) fragment. Taken together, our study revealed a new function for Prx4 enzyme and established a new enzyme-type ligand for activation of the JAK/STAT pathway in an aquatic arthropod.